INVESTIGATION OF THE TECHNOLOGY OF VACUUM DEGASSING OF STEEL AT FACILITY OF BOWL DEGASIFYING TREATMENT - N. V. Andrianov; S. V. Terletskij; A. V. Olenchenko (Литьë и металлургия)
The factors, influencing on efficiency of carrying out of vacuum processing of steel at bowl vacuumator VD, are revealed. The deficiencies of the existing technology are determined and recommendations on changing of the technological parameters are worked out.